Análise e implementação de estruturas de controle em dispositivo FPGA aplicadas a um conversor Buck - Lucas, Ricardo (2015)
This work discuss several techniques of control, with an intention of comparison of performance and robustness to apply them to Buck coverter. Starting with PID (Proportional, Integral, Derivative) controller, widely explored and dominated in an industrial environment, it’s used in this work as comparison reference for the others techniques developed. Another strategy presented here is the GANLPID (Gaussian Adaptative Non LinearPID), it’s a case of non linear technique, has won variants in function of the based on a Gaussian error function. variants have gains on function of error based on a Gaussian function. The pole placement control technique not having full part in their basic forms, being necessary to include this term to eliminate the steady-state error. The main performance analysis features are the settling time and overshoot. All the techniques are explored in order to be implemented in FPGA (Field Programmable Gate Array) devices, having some advantages over microcontrollers and DSP’s (Digital Signal Processor), because can execute tasks in parallel allowing the implementation of the algorithm more faster. The chosen control techniques were simulated using the DSP Builder tool and and compiled directly in HDL (hardware description language) code. The results of simulation and experimental are presented and discussed in order to validate the proposed projects.